Trade Dimensions of Logistics Services : A Proposal for Trade Agreements - Kunaka, Charles (World Bank, Washington, DC, 2013)
Services have a direct impact on the competitiveness of the goods sector. This paper illustrates the importance of logistics services, their trade dimension, and how regulatory issues act as perhaps one of the most significant barriers to competitiveness. The paper discusses recent developments and the role and benefits of logistics services and argues that from a trade agreement standpoint, logistics is a network industry that ultimately provides one service to a final client. It analyzes logistics services from a services trade perspective and proposes that trade agreements should ensure access to and use of the infrastructure required to provide these services recognizing their interconnectedness. The paper offers suggestions on additional policies World Trade Organization members, and countries negotiating services agreements regionally or bilaterally, could follow in order to fully exploit the opportunities provided by logistics services. Local regulations and complementary policies in areas such as trade facilitation will always remain important.